Knowledge and Awareness of the Diagnostic Process and Access to Services for Children with Autism Spectrum Disorders among Professionals and Community Members in Two Countries - Stankova, Margarita; Ivanov, Ivan; Mihova, Polina; Proedrou, Alexandros (Journal of Intellectual Disability - Diagnosis and Treatment, 2026)
The study examines autism awareness in two countries, focusing on knowledge of the diagnostic process and support for children and their families. 1,618 participants /1,052 - Bulgaria and 566 - Greece/ were provided with an online survey that contained statements about the most important reasons why parents seek professional help, the prognosis of the disorders, and the inclusion process. The results show that participants from both countries report stereotyped and other ritualistic behaviors, social dysfunctions, and speech and language dysfunctions as significant reasons for parents to consult professionals about their children. Participants from Bulgaria placed greater importance on the first two characteristics. The participants also responded relatively positively to the statement that children with autism can grow up to live independent lives, have jobs, income, and families, and even more supported the statement that “Early interventions and therapies can lead to significant improvements in the social and communication skills of children with autism”, with participants from Bulgaria showing more support for both statements.